Integrating Global Issues into Kurikulum Merdeka Development in Teacher Education: A Case Study of UPI Bandung - Boby Yasman Purnama; Kasful Anwar Us; Fridiyanto, Fridiyanto (Tinta Emas Institute, 2025)
Integrating global issues into teacher education curricula is essential for preparing future educators with global competence—the ability to understand global challenges, respect diverse perspectives, and act toward sustainable development. This study investigates the strategic integration of global issues into the development of the Kurikulum Merdeka at Universitas Pendidikan Indonesia (UPI) Bandung. Using a qualitative case study approach, data were collected through semi-structured interviews with faculty members, program heads, and curriculum developers, supported by document analysis and participatory observation. The findings show that UPI has taken progressive steps in integrating global themes—such as sustainability, social justice, global literacy, and digital citizenship—into courses, student projects, and academic collaborations. Initiatives like Collaborative Online International Learning (COIL) and SDG-based community service programs highlight UPI’s commitment to global education. However, implementation remains uneven across departments, with challenges such as limited faculty training, insufficient digital infrastructure, and a lack of shared understanding regarding the importance of global competencies. The study concludes that a systemic and institutionalized approach is required to embed global literacy as a core element of teacher education. Strengthening faculty capacity, curriculum flexibility, and international collaboration will be key to ensuring that future teachers are not only locally grounded but also globally responsive.